Penyusunan Rencana Mitigasi Bencana dalam Upaya Penguatan Kapasitas Pengelola Wisata Desa Biting Kecamatan Badegan Kabupaten Ponorogo - Adam Hilman, Yusuf; Khoirurrosyidin, Khoirurrosyidin; Yusdiawan Azhar, Insyira; Rivatul Mahmuddah, Helda (Abdimas Indonesian Journal, 2024)
Tourism is a sector that can be relied upon to increase economic growth, so it is necessary to organize and manage tourist destinations well and professionally, the demand for professionalism is an important thing that must be realized for destinations for the sake of security and comfort so that the destination can run sustainably, in an effort In achieving these conditions, a problem arises, namely the unpreparedness of tourist destination managers for disaster events that can arise at any time without warning, which can disrupt the safety and comfort of travelers. This study aims to look at the efforts of tourism managers in preparing for disaster events through the concept of disaster mitigation. The method used in this study begins with a Focus Group Discussion activity to carry out several activities, including: 1). Mapping and creating information on village potential, 2). Forming a disaster task force, 3). Developing disaster response skills, 4). Simulation of disaster management, 5). Evaluation of disaster mitigation activities. From the activities carried out, we can see changes in understanding and increased mitigation skills possessed by tourist destination managers. This tells us that there is an increase in capacity experienced by tourism managers to become more skilled and capable.